Effect of variable rumen degradable nitrogen levels on microbial protein synthesis estimated with purine derivatives in sheep urine and PDC index - CHANDRASEKHARAIAH, M; THULASI, A; SAMPAT, K T (The Indian Journal of Animal Sciences, 2010)
An experiment was conducted to study the effect of varying rumen degradable nitrogen (RDN) levels on microbial protein synthesis in sheep by measuring excretion of purine derivatives in spot urine samples and purine derivatives: creatinine (PDC) index. Sheep (30) were divided into 5 groups of 6 each and the animals in all groups were fed fingermillet straw (FMS) as a basal diet and soybean extraction as a nitrogen source. The animals in group 1 were fed with ad lib. FMS. Animals in group 2, 3, 4 and 5 were offered soybean extraction@ 16.16, 20.65, 24.75 and 26.64 g RDN/kg DOM along with FMS. The experimental feeding was continued for 2 months followed by metabolism trial. The purine derivatives (mmol/litre) excretion and PDC index were 18.74 and 34.37; 17.88 and 40.68; 20.82 and 42.62; 15.92 and 49.36 and 16.92 and 45.62; 15.92 and 49.36 and 16.92 and 45.44, in group 1 through 5, respectively. The microbial purine absorption, the microbial nitrogen (MN) supply (g/d) were comparable among the RDN supplemented groups. Purine nitrogen index (PNI) and nitrogen conversion efficiency (NCE) values were 0.10 and 1.17; 0.10 and 0.78; 0.07 and 0.65 and 0.06 and 0.62, respectively, in G 2 through 5. The result indicated that 16.16 g RDN from soybean extraction may be adequate for optimum microbial protein synthesis in sheep fed on FMS based diet.